Role of lymphocyte-to-C-reactive protein ratio in forecasting microvascular obstruction in ST-segment elevation myocardial infarction post-percutaneous coronary intervention - Liu, Jiahua; Du, Xinjia; Ren, Yanfei; Mei, Yan; Chen, Lei; Lu, Yuan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCurrent research suggests that microvascular obstruction (MVO) following the first percutaneous coronary intervention (PCI) in myocardial infarction patients is closely related to inflammatory responses. The lymphocyte-to-C-reactive protein (CRP) ratio (LCR), as a novel inflammatory marker, is associated with the prognosis of patients with ST-segment elevation myocardial infarction (STEMI). However, the relationship between LCR and MVO remains unclear. This study aims to investigate the correlation between LCR and MVO in STEMI patients undergoing PCI.MethodsThis was a single-center retrospective study. We consecutively enrolled STEMI patients who underwent PCI at Xuzhou Medical University Affiliated Hospital, Xuzhou, China, from September 2019 to December 2023. Cardiac magnetic resonance (CMR) imaging with late gadolinium enhancement (LGE) was used to assess infarct size and the presence of MVO.ResultsA total of 551 patients were included in this study, with 267 (48.5%) experiencing MVO. The median time for CMR imaging-based detection of MVO was 5 days (interquartile range: 4, 6). Univariate regression analysis revealed that age, white blood cell count, neutrophil count, left ventricular ejection fraction (LVEF), peak N-terminal pro-B-type natriuretic peptide (NT-proBNP), peak high-sensitivity troponin T (hs-TnT), LCR, LGE percentage (LGE%), and MVO percentage (MVO%) were significantly associated with MVO (p < 0.05). Multivariate regression analysis identified LCR as an independent predictor of MVO [Odds Ratio = 0.18, 95% Confidence Interval (CI): 0.04–0.75, p = 0.019]. Receiver operating characteristic curve analysis demonstrated that LCR had predictive capability for MVO, with a sensitivity of 80.1% and specificity of 45.4% when the LCR value was 0.091 [area under the curve (AUC): 0.654, 95% CI: 0.609–0.700, p < 0.001]. A new predictive model incorporating LCR improved the prediction of MVO occurrence (AUC = 0.815, p < 0.001), with significant differences in net reclassification improvement (p = 0.004) and integrated discrimination improvement (p = 0.023) between the new and old models.ConclusionA low LCR is an independent risk factor for MVO after PCI in STEMI patients. The predictive model incorporating LCR enhances the ability to predict MVO occurrence in patients with STEMI post-PCI.